Simulations of different power intensity inputs towards pressure, velocity & cavitation in ultrasonic bath reactor - Mat-Shayuti, M.S. (Elsevier B.V., 2020)
Various ways exist to describe power intensity in ultrasonic system, causing complications in reporting and benchmarking. This paper attempts to compare computational fluid dynamic (CFD) simulations of ultrasonic bath running at 60 W 40 kHz using different power intensity (also known as sound intensity) inputs viz rated power, calorimetric power and particle velocity. Applying Schnerr and Sauer model based on Rayleigh-Plesset equation, an abrupt streaming flow was observed during the transient period. After steady ultrasonic cycle was reached, the simulation using rated power input recorded the highest and widest ranges of total pressure (-51.1 to 308 kPa), fluid particles velocity (7.22 to 11.5 m/s) and cavitation mass transfer (-821 to 925 kg/m3). The sound amplitude around 200 kPa in the rated power intensity generated the greatest cavitation effects, while particle velocity having 23 kPa sound amplitude failed to produce any cavitation bubbles. The difference lay in the tendency of liquid molecules to vaporize (and vice versa) during sound wave oscillation. Verification with experimental data implied the rated power feed produced the closest similarity among the three inputs. Â© 2020 The Author(s)